Pengaruh Edukasi Gizi Menggunakan Media Cakram Gizi Terhadap Pengetahuan dan Perilaku Konsumsi Buah dan Sayur Pada Remaja - Shafira Sulviani; Ratih Kurniasari; Milliyantri Elvandari (Jurnal Ilmiah Wahana Pendidikan, 2022)
Consumption of fruit and vegetables according to the 2018 Riskesdas data shows that the Indonesian population aged 10 years has a tendency to consume less vegetables and fruit according to the standard balanced nutrition guidelines, which is less than 400 grams/person/day consisting of 250 grams of vegetables and 150 grams of fruit in a day. 95.5%. This study aims to analyze the effect of fruit and vegetable nutrition education using nutrition disc media on improving adolescent nutritional knowledge and attitudes at SMA Negeri 1 Cikarang Barat. This study used a quasi-experimental design using pre-test and post-test using a control group with 42 respondents. The results of the study on the age of the majority of the respondents were 17 years old (61.9%), in the gender the majority were women (64.3%). The majority of respondents' knowledge of fruit and vegetable consumption in the pre-test of the intervention group was in the sufficient category (61.9%), and the post-test was in the good category (85.7%), and the behavior of fruit and vegetable consumption of the respondents in the pre-test of the intervention group. included in the poor category (95.2%), and the post-test was in the good category (71.4%). Significant test results were obtained, namely knowledge of fruit and vegetable consumption with a value (p = 0.01), and fruit and vegetable consumption behavior with a value (p = 0.01). The conclusion of this study showed that there was a significant change in knowledge and behavior of fruit and vegetable consumption after being given an intervention using nutritional disc media compared to the control group